MODEL STUKTURAL BERBASIS SISTIM INFORMASI GEOGRAFIS DALAM PENGELOLAAN WILAYAH PESISIR SECARA BERKELANJUTAN - Pieter Th. Berhitu (ALE Proceeding, 2021)
Geographical Information System-Based Structural Model in Sustainable Management of Coastal Areas which is the background is that the management of the coastal areas of Ambon City and Central Maluku Regency in the last 10-20 years has not been managed properly and sustainably so that various aspects of development do not work well causing various The problems include damage to the coastal physical environment, namely abrasion, erosion, and sedimentation, water damage due to pollution, damage to protective building infrastructure, coastal mitigation issues, declining quality of coastal environmental resources due to the increasing number of residents in coastal areas, causing the development of slum areas. coastal ecosystem. The purpose of the study is to determine the model and strategy for managing coastal areas in Ambon City and Central Maluku District in a sustainable manner. The method used in this research is the descriptive method. Primary data collection was carried out using a questionnaire for respondents from the community, expert respondents, community institutions, and policymakers. The analysis carried out is Sustainability Analysis with Multi Dimension Scale (MDS), geographic information system analysis, SEM structural analysis, Process Hierarchy analysis (AHP). The results of the sustainability analysis with MDS obtained the Multi-Dimensional Sustainability Index value of 50.13% is in the moderately sustainable category. The results of the SEM model analysis on the role of zoning and community roles in sustainable coastal area management is an acceptable â€œfit modelâ€. The results of the AHP provide an overview of the assessment by policymakers in the implementation of the program, prioritizing the strategy for Management of Sustainable Coastal Area Management Based on Geographic Information Systems with an assessment score of 39.3%, with the largest presentation being â€œCoastal Area Arrangement in accordance with GIS-Based Zoning Lawsâ€ of 13, 6%.